Identifikasi Berbagai Olahan Ikan Dalam Pemberdayaan Masyarakat Desa Banyu Biru Pandeglang Banten - Raudah Zaimah Dalimunthe; Herlina Siregar (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
Preliminary studies conducted obtained information that the problems often faced by fish processing business groups are knowledge of processed fish production, design and management in terms of variations in fish food processing, such as: salted fish, pindang fish, otak-otak fish. The results of direct observation (January 20, 2020), This fish processing business has been occupied for generations from the family where the sales have decreased from year to year due to climate change and the absence of technology that supports food variety. Therefore, knowledge of processed fish production, design, and entrepreneurial management is needed, so that fish processing can be maximized. The approach and method used in this research is a descriptive qualitative approach. The collection of data and information was carried out through observation and interviews with 10 respondents who were parents. The results of this study indicate that there is still a lack of skills and understanding of the Teluk Village community in managing fish in a variety of processed foods, so that there is a need for follow-up to be given to improve the understanding and skills of the village community.